2014
DOI: 10.1007/s12040-014-0462-8
|View full text |Cite
|
Sign up to set email alerts
|

Ichnofabric analysis of the Tithonian shallow marine sediments (Bhadasar Formation) Jaisalmer Basin, India

Abstract: The shallow marine sedimentary sequence of the Jaisalmer Basin exhibits one of the important and well-developed Tithonian sedimentary outcrops for western India. The ichnology and ichnofabric of the lower part of Bhadasar Formation (i.e., Kolar Dongar Member) belonging to Tithonian age are presented and discussed. The Kolar Dongar Member represents a shallow marine succession that contains 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…It is a well established fact that trace fossils can be used in the interpretation of paleoenvironment of depositional basin (McIlroy 2004;Miller 2007;Rodriguez-Tovar 2010). In the Indian context, a number of ichnological studies have been carried out recently on various stratigraphic horizons ranging in age from Cambrian to Miocene primarily from peninsular India, to understand their depositional environments (Patel et al 2008Malarkodi et al 2009;Nagendra et al 2010;Saha et al 2010;Joseph et al 2012;Srivastava and Mankar 2012;Chakraborty et al 2013;Desai and Saklani 2014;Kulkarni and Borkar 2014;Pandey et al 2014;Patel 2014). But ichnological research of the Palaeogene succession of Indo-Myanmar ranges is very scanty.…”
Section: Introductionmentioning
confidence: 99%
“…It is a well established fact that trace fossils can be used in the interpretation of paleoenvironment of depositional basin (McIlroy 2004;Miller 2007;Rodriguez-Tovar 2010). In the Indian context, a number of ichnological studies have been carried out recently on various stratigraphic horizons ranging in age from Cambrian to Miocene primarily from peninsular India, to understand their depositional environments (Patel et al 2008Malarkodi et al 2009;Nagendra et al 2010;Saha et al 2010;Joseph et al 2012;Srivastava and Mankar 2012;Chakraborty et al 2013;Desai and Saklani 2014;Kulkarni and Borkar 2014;Pandey et al 2014;Patel 2014). But ichnological research of the Palaeogene succession of Indo-Myanmar ranges is very scanty.…”
Section: Introductionmentioning
confidence: 99%
“…5B and 9C). These ichnotaxa have usu ally been re ported from en vi ron ments ranging from the lower shoreface to off shore (Desai and Saklani, 2014;Wilmsen and Niebuhr, 2014a;MacEachern and Bann, 2020). More over, Planolites beverleyensis ap pears also in a Thalassinoides infill (Fig.…”
Section: Ichnological Implications On Depositional Environmentmentioning
confidence: 99%
“…Re marks. -The bur row re sem bles Ancorichnus, which is char ac ter ized by a cen tral (in ner) meniscate fill ing and a struc tured, un du lat ing man tle or tube-shaped outer fill (see Heinberg, 1974;Dam, 1990;Keighley and Pickerill, 1994;Desai and Saklani, 2014). Ac cord ing to the cited au thors, the man tle is not con sid ered as a wall struc ture since it was formed by the lo co mo tive be hav ior of the bur row pro ducer.…”
Section: Description Of Trace Fossilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of hydrocarbon-bearing reservoir lithofacies has been identified based on this comparison study, where changes in the AI property have been identified. The study area is surrounded by multiple high gravity structures, many of which are oil and gas fields (Desai and Saklani 2014): Bakhri Tibba, Vikhran Nai, Manhera Tibba, and Ghotaru ( DGH 2007).…”
Section: Introductionmentioning
confidence: 99%